Coatings of Different Carbon Nanotubes on Platinum Electrodes for Neuronal Devices: Preparation, Cytocompatibility and Interaction with Spiral Ganglion Cells. - Niklas Burblies; Jennifer Schulze; Hans-Christoph Schwarz; Katharina Kranz; Damian Motz; Carla Vogt; Thomas Lenarz; Athanasia Warnecke; Peter Behrens (PLoS ONE, 2016)
Cochlear and deep brain implants are prominent examples for neuronal prostheses with clinical relevance. Current research focuses on the improvement of the long-term functionality and the size reduction of neural interface electrodes. A promising approach is the application of carbon nanotubes (CNTs), either as pure electrodes but especially as coating material for electrodes. The interaction of CNTs with neuronal cells has shown promising results in various studies, but these appear to depend on the specific type of neurons as well as on the kind of nanotubes. To evaluate a potential application of carbon nanotube coatings for cochlear electrodes, it is necessary to investigate the cytocompatibility of carbon nanotube coatings on platinum for the specific type of neuron in the inner ear, namely spiral ganglion neurons. In this study we have combined the chemical processing of as-delivered CNTs, the fabrication of coatings on platinum, and the characterization of the electrical properties of the coatings as well as a general cytocompatibility testing and the first cell culture investigations of CNTs with spiral ganglion neurons. By applying a modification process to three different as-received CNTs via a reflux treatment with nitric acid, long-term stable aqueous CNT dispersions free of dispersing agents were obtained. These were used to coat platinum substrates by an automated spray-coating process. These coatings enhance the electrical properties of platinum electrodes, decreasing the impedance values and raising the capacitances. Cell culture investigations of the different CNT coatings on platinum with NIH3T3 fibroblasts attest an overall good cytocompatibility of these coatings. For spiral ganglion neurons, this can also be observed but a desired positive effect of the CNTs on the neurons is absent. Furthermore, we found that the well-established DAPI staining assay does not function on the coatings prepared from single-wall nanotubes.